UNSTEADY FRICTION AND HEAT TRANSFER IN THE INITIAL PIPELINE SECTION AT THE RESET OF THERMAL LOAD - K. H. Gilfanov; N. D. Yakimov; N. Y. Minvaleev; E. G. Sheshukov; N. W. Bogdanova (Известия высших учебных заведений: Проблемы энергетики)
The results of numerical and experimental study of wall friction and heat transfer in a short cylindrical channel are presented. Hydrodynamic and thermal characteristics of nonstationary high-temperature gas flow are determined. The results are summarized in the framework of boundary layer theory.